The Effectiveness of KUR Sharia Products in PT. Pegadaian Talise Branch UPC Tawaeli in SME Development - Rifqah Fadhilah; Santi Yunus; Haerul Anam; Rita Yunus; M. Anwar Nasruddin (Golden Ratio of Data in Summary, 2024)
PT. Pegadaian as a financial institution has an important role in providing financing for sharia-based SME as part of an effort to support this real sector. This study aims to determine the impact and benefits of using KUR Syariah and analyze the effectiveness of KUR Syariah products in \ the development of SME. The research method used is descriptive qualitative. The results of this study indicate that KUR Syariah products are effective in supporting the development of SME and have a very positive impact on MSME actors, and the benefits obtained through financing are business development and easier financial management. This research found several aspects to improve the effectiveness of Sharia KUR products at PT. Pegadaian, including consistent goals, consistent time, quantity provisions, and credit provisions. The four ways to measure the effectiveness of KUR products are very precise based on the consistency of targets, quantity and time in applying or distributing KUR. Therefore, in this case it can be said that the Sharia KUR Products distributed by PT. Pegadaian UPC Tawaeli are considered effective and right on target.